TANGGUNG JAWAB HUKUM FISIOTERAPIS YANG MELAKUKAN PELAYANAN KESEHATAN TANPA SURAT TANDA REGISTRASI - Ranggih Ade Atmaja; Sarsintorini Putra (Masyarakat Hukum Kesehatan Indonesia, 2022)
Medical personnel and health workers or competent personnel to restore someone who is sick are required to have a Registration Certificate. It's the same with physiotherapists. The use of STR for practice requirements applies to physiotherapists. This provision has been explained in the Minister of Health of the Republic of Indonesia Number 80 of 2014 concerning the Implementation of Physiotherapy Work and Practices Article 4 Paragraph (1) has explained that Physiotherapists must have STR, Indonesia itself still many who violate it. The occurrence of similar cases is due to the causative factors for which a solution will be needed later. The purpose of this study is to determine the legal responsibilities. This research method uses the normative method. In resolving this case by applying legal responsibilities such as providing criminal sanctions in accordance with Law Number 36 of 2014 concerning Health Workers Article 85 paragraph (1), for Indonesian Physiotherapists, and Article 2 for Foreign Physiotherapists. There are several factors that cause this problem to form, therefore efforts are needed such as improving the government bureaucracy, conducting supervision, providing information to colleagues related to STR. The advice is to implement all of them well.